2011
DOI: 10.1007/s11033-011-0757-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a simple loop-mediated isothermal amplification method on rapid detection of Listeria monocytogenes strains

Abstract: A loop-mediated isothermal amplification (LAMP) method for rapid detection of the food-borne L. monocytogenes strains had been developed and evaluated in this study. The optimal reaction condition was 65 °C for 45 min, with the detection limit as 1 pg DNA/tube and 100 CFU/reaction. Application of the established LAMP assay was performed on 182 food-borne L. monocytogenes strains using a rapid procedure and easy result confirmation, with the sensitivity of LAMP versus PCR assays as 96.7% (176/182) and 91.2% (16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 23 publications
1
53
0
1
Order By: Relevance
“…Regarded as one of the greatest contributions to medicine and humanity in the 20th century, antibiotics had been used to treat a wide range of infectious diseases caused by bacteria, for both animals and humans. Microorganisms mediated infectious diseases still remain one of the greatest concerns in public health (Wang et al, , 2012Zhao et al, 2010aZhao et al, , b, c, 2011Xu et al, 2011dXu et al, , 2012a. However, the indiscriminate use of existing antibiotics leads to the emergency of antibiotic resistance and poses a dilemma for the future treatment of bacterial infection, with an increasing number of clinical failures in bacterial mediated *Corresponding authors.…”
Section: Introductionmentioning
confidence: 99%
“…Regarded as one of the greatest contributions to medicine and humanity in the 20th century, antibiotics had been used to treat a wide range of infectious diseases caused by bacteria, for both animals and humans. Microorganisms mediated infectious diseases still remain one of the greatest concerns in public health (Wang et al, , 2012Zhao et al, 2010aZhao et al, , b, c, 2011Xu et al, 2011dXu et al, , 2012a. However, the indiscriminate use of existing antibiotics leads to the emergency of antibiotic resistance and poses a dilemma for the future treatment of bacterial infection, with an increasing number of clinical failures in bacterial mediated *Corresponding authors.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors reported that LAMP is more sensitive and less influenced by components of biological samples than conventional PCR and real time PCR [12] [16] [17]. Although we did not compare herein the LAMP with other technologies, one can expect that our protocol would be successfully applied for biological samples.…”
Section: Discussionmentioning
confidence: 94%
“…LAMP assays for diagnosing L. monocytogenes infection have previously been reported [12] [16] [17]. Although these techniques are more sensitive than the LAMP we present here, none of them intended species detection with serotypes distinction.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations